KINERJA KARYAWAN: PERAN GAYA KEPEMIMPINAN DAN KEPUASAN KERJA - Ritonga, Wier; Tun Ganyang, Machmed (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to examine the relationship between leadership, job satisfaction, and employee performance. Design/methodology/approach- A total of 45 respondents were used as research samples through questionnaires. Data were analyzed using the path analysis approach with the help of the LISREL program. Findings- The results show that leadership has a positive and significant effect on job satisfaction and performance, and job satisfaction has also been shown to have a significant effect on performance. Implications-The results of this study suggest that managers put forward a democratic and supportive style to improve employee job satisfaction through providing opportunities to subordinates to provide ideas/suggestions in various decisions taken by the company, Keywords: performance, satisfaction, leadership style